The Role of Religious Actors in Dialogues For Peacebuilding and Conflict Prevention in Afghanistan: A Case Study in The Faculty of Shari’a (Islamic) Law And The Faculty of Public Policy, Kabul University - Zarghoni, Mohammad Afzal (Jurnal Ilmiah Ilmu Ushuluddin, 2022)
This study examines the role of religious actors (the Ulema) in dialogues for peacebuilding and conflict prevention in Afghanistan by surveying third and fourth year students in two faculties of the University of Kabul (Faculty of Shari’a (Islamic) Law and Faculty of Public Law. The results indicate an overall positive view of the role of religious actors, with consistent views about helpful results accruing from the involvement of the Ulema in dialogue within communities to cope with crises, conflict and disagreements.